Community intervention trial for estimating risk of acute gastrointestinal illness from groundwater-supplied non-disinfected drinking water - Mark A. Borchardt; Burney A. Kieke; Susan K. Spencer; Elisabetta Lambertini; Tucker R. Burch; Frank J. Loge (IWA Publishing, 2023)
By community intervention in 14 non-disinfecting municipal water systems, we quantified sporadic acute gastrointestinal illness (AGI) attributable to groundwater. Ultraviolet (UV) disinfection was installed on all supply wells of intervention communities. In control communities, residents continued to drink non-disinfected groundwater. Intervention and control communities switched treatments by moving UV disinfection units at the study midpoint (crossover design). Study participants (n = 1,659) completed weekly health diaries during four 12-week surveillance periods. Water supply wells were analyzed monthly for enteric pathogenic viruses. Using the crossover design, groundwater-borne AGI was not observed. However, virus types and quantity in supply wells changed through the study, suggesting that exposure was not constant. Alternatively, we compared AGI incidence between intervention and control communities within the same surveillance period. During Period 1, norovirus contaminated wells and AGI attributable risk from well water was 19% (95% CI, −4%, 36%) for children <5 years and 15% (95% CI, −9%, 33%) for adults. During Period 3, echovirus 11 contaminated wells and UV disinfection slightly reduced AGI in adults. Estimates of AGI attributable risks from drinking non-disinfected groundwater were highly variable, but appeared greatest during times when supply wells were contaminated with specific AGI-etiologic viruses. HIGHLIGHTS Community intervention study estimated illness risk from non-disinfected groundwater.; Ultraviolet light disinfection installed on community drinking water wells.; Measured viruses in wells by qPCR; acute gastrointestinal illness by health diaries.; Attributable risk estimates obtained for endemic AGI from drinking groundwater.;